Novel Dimethylacetamide-Containing Formulation Improves Infraorbital Anaesthesia Efficacy in Rats with Periodontitis - Ekaterina V. Blinova; Evgeniia V. Shikh; Elena V. Semeleva; Aleksandra M. Yurochkina; Andrey V. Novikov; Anna P. Vediaeva; Arkadii B. Lebedev; Elena G. Lobanova; Olga V. Vasilkina; Dmitry S. Blinov; Yan A. Mazov; Evgeniia A. Kogan (Hindawi Limited, 2020)
Background. To evaluate acute toxicity and local anaesthetic activity of a formulation containing a novel dimethylacetamide derivative, antioxidant, and vasoconstrictor in rats with chronic periodontitis. Methods. Novel anaesthetic dimethylacetamide-containing formulation LHT-15-32 was studied as 2% water solution. Its acute intravenous and subcutaneous toxicity was determined in mice. Pain sensitivity threshold of the upper second molar was determined in rats with experimental periodontitis. Oxidative stress activity and total antioxidant capacity were determined in rats' gingival mucosa by induced chemiluminescence. Local changes were evaluated in periodontal tissue by morphological examination. Tissue IL-1β, IL-10, and TNF-α concentration was quantitatively assessed by an enzyme-linked immunosorbent assay. LHT-15-31 Na-blocking activity was studied on isolated neurons of Limnaea stagnalis' parapharyngeal ganglion. Isolated sciatic nerve of Rana radibunda was perfused with different concentrations of LHT-15-32 to assess its conductivity. Statistical analysis was used, and continuous variables were presented as mean ± square deviation. The normality of distribution was determined using ANOVA. Newman-Keuls parametric criterion was used for intergroup comparison. LD50 indexes were calculated by probit analysis. Results. LHT-15-32 acute intravenous and subcutaneous toxicity was lower than that of its active substance. The formulation by infraorbital administration induced deep dental anaesthesia which lasted over 70 min and activated the local antioxidant defense system and decreased IL-1β level in gingival tissue. LHT-15-32 triggered tissue reparation around the impacted upper molar in rats assessed five days after administration. At 10−6 to 10−3 M concentration, LHT-15-32 inhibited sciatic nerve conductivity and blocked Na+ channels of isolated neurons in a dose-dependent manner. Conclusions. The formulation may be considered as an effective and safe approach to anaesthetize upper molars with periodontitis.